Evaluasi Program Pengelolaan Sampah Tempat Pembuangan Akhir (TPA) Wisata Edukasi Talangagung (Studi pada Dinas Cipta Karya dan Tata Ruang Kabupaten Malang) - Putra, Alfian Prasadana (Jurnal Administrasi Publik, 2016)
Abstact: Evaluation Of Waste Management Program At Final Disposal Place Edutainment Of Talangagung (Study in Department of Human Settlements and Spatial Plan- ning Malang Regency). Trash known as useless things and Final Disposal Place known as a place that should never be visited. Yet all those stereotype is invalid when it comes to Final Disposal Place Edutainment of Talangagung that has waste management program which environmental friendly and has benefit for peo- ple as well. Final Disposal Place Edutainment of Talangagung has comfortable and beautiful environment, the place has playground, gazebo and Methane Converter. While the visitors enjoying the comfortable place, they also given education about waste management for environmentally friendly purpose, as well as how the methane converter works and get financial benefit by joining Waste Bank Program. Final Disposal Place Edutainment Talangagung well known as one of the best in Indonesia, that’s proven by so many visitor from another local government and student for comparative study or research purpose. No wonder that Final Dis- posal Place Edutainment of Talangagung get award each year.   Keywords: Evaluation, Program, Waste Management, Edutainment   Abstrak: Evaluasi Program Pengelolaan Sampah Tempat Pembuangan Akhir (TPA) Wisata Edukasi Talangagung. (Studi pada Dinas Cipta Karya dan Tata Ruang Kabu- paten Malang). Sampah dikenal sebagai barang yang tidak berguna dan TPA dikenal sebagai tempat yang tidak layak dikunjungi, namun hal itu tidak berlaku di TPA Wisata Edukasi Talangagung, TPA Talangagung memiliki program pengelolaan sampah yang ramah lingkungan dan juga bermanfaat bagi masyarakat. TPA Talangagung memiliki lingkungan yang asri dan sejuk bahkan memiliki arena bermain anak, gazebo dan alat peraga pengelolaan gas menjadi gas metan. Selagi menikmati TPA yang nyaman, pengunjung diajarkan cara pengelolaan sampah dan juga pengelolaan gas metan sehingga dapat berguna bagi masyarakat sebagai peng- ganti LPG. Selain itu di sini juga terdapat program bank sampah yang memberikan manfaat secara finansial kepada masyarakat. TPA Talangagung dikenal sebagai TPA percontohan di Indonesia terbukti dari banyaknya kunjungan dari kalangan pemerintah daerah dan mahasiswa, tidak heran apabila TPA ini telah menerima berbagai macam penghargaan setiap tahunnya.   Kata kunci: Evaluasi, Program, Pengelolaan Sampah, Edutainment